Layanan Informasi Program Usaha Mikro, Kecil, dan Menengah Kota Makassar (Survei di Kelurahan Bira, Kecamatan Tamalanrea dan Kelurahan Kunjungmae, Kecamatan Mariso) - Rukman Pala; Rachmawaty Djaffar (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
The rapid development of information makes the government must keep up with existing developments. The need for the use of information technology due to Indonesia's vast territory.Information services are carried out by the government to disseminate programs to the public including the MSME programs. However, the obstacles faced are the media and information channels that are less capable of being used as a source of information that disseminate the MSME programs. This study aims to find out how the MSME program information services in Makassar City, especially in the Bira Subdistrict-Tamalanrea District and Kunjungmae Subdistrict-Mariso District. The research method used was a survey with a quantitative approach with 121 research respondents. The results of the study conclude that respondents do not use official government media in the field of communication and information (central and regional) in seeking information. However, several topics of information that were of concern to respondents, including internet sites and social media, were very little used by respondents in accessing information services. Information channels as a source of information about the MSME program launched by the government were mostly obtained from banners/billboards posted by related agencies. Information services through information media that are used by the public to obtain MSME information services mostly come from television and from family members through direct communication as well as via email and social media.